2021
DOI: 10.1681/asn.2021030336
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Tubular Secretion of Organic Solutes in Advanced Chronic Kidney Disease

Abstract: Background The clearance of solutes removed by tubular secretion may be altered out of proportion to the glomerular filtration rate (GFR) in chronic kidney disease (CKD). Recent studies have described considerable variability in the secretory clearance of waste solutes relative to the GFR in patients with CKD. Methods To test the hypothesis that secretory clearance relative to GFR is reduced in patients approaching dialysis, we used metabolomic analysis to identify solutes in simultaneous urine and plasma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…So far, several studies have reported that PAG showed different levels of content during various disease states [35][36][37], but a strong correlation between PAG and DSPN phenotype has never been reported. As outlined previously, Unabsorbed Phe could be oxidized and metabolized by Clostridium sporogenes in the intestinal flora and involved in PAG synthesis [18,38].…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies have reported that PAG showed different levels of content during various disease states [35][36][37], but a strong correlation between PAG and DSPN phenotype has never been reported. As outlined previously, Unabsorbed Phe could be oxidized and metabolized by Clostridium sporogenes in the intestinal flora and involved in PAG synthesis [18,38].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hyperbilirubinemia, cholemic nephropathy (also termed cholemic nephrosis, cholemic nephropathy, or bile cast nephropathy) refers to a condition characterized by intratubular bile casts with impaired kidney function in the setting of cholestasis (30). It was originally described in individuals with cholangiocarcinoma or other causes of obstructive jaundice (38). The notion that cholemic nephropathy is implicated in the pathogenesis of HRS-1 was introduced by human autopsy studies reporting a significant proportion of patients with cirrhosis with histologic evidence of intratubular bile casts who had been diagnosed as having HRS-1 premortem (39,40).…”
Section: Etiology-driven Management Of Aki In Cirrhosismentioning
confidence: 99%
“…They pass through different transporters on the apical membrane into the tubule lumen, where they then act at their respective tubule sites. Numerous uremic solutes are cleared by these same secretory mechanisms, and their secretion may be impeded by competing diuretics (3). However, our study showed no impairment in secretion of four uremic solutes in the setting of furosemide use in patients receiving hemodialysis.…”
mentioning
confidence: 99%
“…Among these eight participants, the daily furosemide dose averaged 221±109 mg at week 5 compared with 48±55 mg at baseline ( P =0.01). Four organic acids normally secreted by the kidneys (phenylacetylglutamine, p-cresol sulfate, indoxyl sulfate, and hippurate) and furosemide were measured using liquid chromatography tandem mass spectrometry (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation